Fazlur Rahman Sebagai Tokoh Pembaharu Islam 1919–1988 M - Isnaini Fauziyatun Nisya (Qurthuba: The Journal of History and Islamic Civilization, 2019)
Abstract: This article discusses the role of Fazlur Rahman as an Islamic reformer. The focus of the research discussed in this thesis are: 1) What is the background of Fazlur Rahman's life and education 2) What is the contribution of Fazlur Rahman's thoughts to the renewal of the Islamic world 3) What is the influence of Fazlur Rahman's thoughts on Muslim scholars in Indonesia. In writing this article the author uses historical research methods with the following steps: heuristics (data collection), verification (data criticism), interpretation (data interpretation) and historiography (historical writing). The writing of this article uses a historical-sociological approach. From the results of the research, the authors conclude that: 1) Fazlur Rahman is a prominent Muslim scientist from Pakistan. He is famous for his Neomodernism thinking. He was born in Hazara on September 21, 1919 to be exact. He was a lecturer at the University of Chicago until his death. 2) as a reformer, Fazlur Rahman produced many thoughts, including the methodology of Al-Qur'an Interpretation, Islamic Law, Islamic Education, and the Concept of an Islamic State. 3) Ahmad Syafii Maarif and Nurcholish Madjid are two prominent Muslim scientists from Indonesia who were influenced by Fazlur Rahman's thoughts. The two of them were Fazlur Rahman's students when they were studying at the University of Chicago. Keywords: Fazlur Rahman, renewal, influence, Indonesia